Processos de formação e práticas docentes na constituição histórica da educação física escolar no Espírito Santo, nas décadas de 1930 e 1940 - Borel, Tatiana (2012)
The study analyzes the establishment of physical education in the Brazilian state of Espírito Santo, in the 1930s and 1940s. As a timeframe, we employ the creation of the Department of Physical Education of Espírito Santo, founded in 1931, and the processes that involve Physical Education in Espírito Santo between 1930 and 1945, when the country was under the leadership of Getúlio Vargas.This work examines the ideas that circulated in the training course at the School of Physical Education of Espírito Santo, founded in 1934, and its relations with the practice of the alumni of the institution at schools of the state, showing the physical education developed at the Gymnasium of Espírito Santo and Kindergarten Ernestina Pessoa, both educational establishments of great importance in the state during the period analyzed. We used the following sources: reports from the School of Physical Education, newspaper clippings, articles published in the Journal of Education (1934 -1937) and Journal of Physical Education (publish by the army - 1933 to 1941), guidelines for teachers, reports of people who experienced scholar physical education, regulations and other documents that indicate how Physical Education was in the state during the period analyzed. This work also describes a historical overview about the issues that were related to the formation of physical education teachers and the practices developed by them at the schools. The propositions of Carlo Ginzburg and Marc Bloch made possible an analysis of the diverse sources found. Among the aspects analyzed, it is worth mentioning: the spaces reserved to the practice, the teaching guidelines, the creation and the role of sporting clubs, teachers who have excelled in this area in the state, and others. The final discussion indicates that the training of physical education teachers in Espírito Santo, despite some structural difficulties, has stood out nationally, serving as a model for other states of Brazil. The physical education at schools of the state, even with the most unfavorable situations, was developed and constantly highlighted in the media, such as in magazines and local newspapers